A companion to the Greek lyric poets - Gerber, Douglas E. (Mnemosyne, Supplements, 1997)
This handbook for the reading of early Greek poetry is intended to be both a manual for teachers and a guide for advanced undergraduate and graduate students. It covers poetry in the elegiac and iambic genres, as well as melic poetry which is provisionally divided into the personal and the public. The book takes a critical look at scholarly trends applied in interpreting this poetry, exploring, for example, the problems of defining the nature of the elegiac genre, the origins of iambic poetry, the personal voice used by the poets, and the validity of historical criticism. Appearing in the Classical Tradition series, it considers the impact of modern literary theory on the reading of these texts - for instance the new interpretations suggested by feminism - and guides readers to a full bibliography on scholarly debates from the 19th century to the present.